Free Flap Reconstruction of the Lower Lip: A Systematic Review and Meta-Analysis - Murray-Douglass, Alexander; Romeo, Pascalino; Fox, Carly (Journal of Reconstructive Microsurgery, 2024)
Background Large defects of the lower lip often require free tissue coverage. Fasciocutaneous free flaps have been traditionally used, but innervated muscular free flaps may fundamentally address orbicularis oris deficiency and improve dynamic competence. This review aimed to determine if innervated muscular free flaps provided benefit over fasciocutaneous free flaps for reconstruction of defects of more than 50% of the lower lip. Outcomes of interest included functional oral outcomes including oral competence, aesthetic outcomes, and patient-reported outcome measures.Methods Five databases (PubMed, Embase, Web of Science, CINAHL, and CENTRAL) were searched for variations of “lip” and “free flap.” Two authors screened articles and included primary research of free flap reconstruction of more than 50% of the lower lip from any etiology in living humans with an English full-text available. Composite bony flaps were excluded. Oral competence and aesthetic satisfaction, reconstruction details, and complications were extracted. Proportional meta-analyses were used to synthesize results for fasciocutaneous free flaps, which were compared with those for muscular free flaps.Results Fifty-nine articles describing 242 patients were included. Muscular free flaps reported significantly higher proportional oral competence than fasciocutaneous free flaps (98 vs. 83%, p = 0.01). Aesthetic outcomes (98 vs. 97%, p = 0.22) and complications (17 vs. 18%, p = 0.79) were equivalent between fasciocutaneous and muscular free flaps.Conclusion Muscular free flaps may address the fundamental orbicularis oris defect that causes oral incompetence and seem to provide better functional results. Aesthetic outcomes and complications seem to be equivalent.
Keywords: lower lip; free flap; reconstruction; cancer; trauma